Editorial Revista Anagramas Volumen 13, numero 25 julio-diciembre de 2014 (2014)
This is issue 13 of our Journal, a proof of our permanent consolidation. In addition to our incursion in platforms such as Isi-Cielo and WebQualis, now we are included in e-revist@s, a portal of significant influence on the field of science in Hispanic America. The more readers can have access to our contents the closer we will be to fulfill our vision: To disclose research results derived from the communication field.  Consequently, issue by issue we are witnessing the expansion of the boundaries of communication knowledge and the academic reflections that emerge from situations experienced in Hispanic America and the entire world. For this reason our pages have been given cooperation in all areas comprising the field of communication and have witnessed the way topics and political and cultural tendencies have formed.